Persepsi Siswa terhadap Komunikasi Interpersonal Guru Matematika dan Implikasinya terhadap Pembelajaran - Vrasetya, Arshinta; Putri, Rahmi; Nasution, Eline Yanty Putri (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
Teacher interpersonal communication is an important factor influencing the quality of both the learning process and learning outcomes, particularly in mathematics, which is often perceived as a difficult subject by students. This study aims to analyze students’ perceptions of the interpersonal communication of mathematics teachers at SMA Negeri 3 Sungai Penuh. The study employed a descriptive quantitative approach involving 25 students as respondents. Data were collected through a closed-ended questionnaire that had been tested for validity and reliability and were supported by classroom observations. The research instrument consisted of five indicators of interpersonal communication: openness, empathy, mutual support, positive attitude, and similarity. The results indicate that students’ perceptions of mathematics teachers’ interpersonal communication are categorized as good, with percentages of 78.25% for openness, 77.75% for empathy, 78% for mutual support, 76.5% for positive attitude, and 85.25% for similarity. However, several aspects still require improvement, particularly in terms of equitable distribution of attention and appreciation of students’ efforts. These findings suggest that improving the quality of teachers’ interpersonal communication has the potential to create a more inclusive, conducive, and effective mathematics learning environment. Therefore, it is recommended that mathematics teachers continuously develop their interpersonal communication skills through reflective teaching practices and ongoing professional development to support the improvement of mathematics learning quality.